Evaluation of the clinical and cost-effectiveness of the York Faecal Calprotectin Care Pathway. Issue 4 (7th June 2018) - Turvill, James; Turnock, Daniel; Holmes, Hayden; Jones, Alison; Mclaughlan, Eleanor; Hilton, Victoria; Marriott, Stacey
Abstract : Objective: To evaluate the sensitivity and specificity of the York Faecal Calprotectin Care Pathway (YFCCP) and undertake a health economics analysis. The YFCCP has been introduced in support of the National Institute for Health and Care Excellence (NICE) guidance DG11. It is designed to improve the sensitivity and specificity of faecal calprotectin (FC) in discriminating the irritable bowel syndrome from inflammatory bowel disease in primary care. Design: To prospectively evaluate the clinical outcomes at 6 months of the first 1005 patients entering the YFCCP. To develop a cost-consequence model using two comparators: one based on clinical assessment and the C reactive protein/erythrocyte sedimentation rate without using FC, and the second using single testing of the standard FC cut-off. Setting: North Yorkshire primary care practices. Patients: Primary care patients fulfilling NICE DG11. Interventions: The YFCCP. Main outcome measures: Clinical outcome measures from secondary care records. Results: The sensitivity and specificity of the YFCCP are 0.94 (0.85 to 0.98) and 0.92 (0.90 to 0.94), giving a negative and positive predictive value of 0.99 (0.98 to 1.0) and 0.51 (0.43 to 0.59), respectively. Conclusions: The YFCCP overcomes the challenges experienced with FC use in primary care, its efficacy matching initial NICE projections. It is readily incorporated into clinical practice. It should represent the framework on which to increase NICE DG11 implementation nationally.